Magnesium Promotes the Regeneration of the Peripheral Nerve - Zhang, Jingxin; Zhang, Binjing; Zhang, Jinglan; Lin, Weimin; Zhang, Shiwen (Frontiers in Cell and Developmental Biology, 2021)
Peripheral nerve injury is a common complication in trauma, and regeneration and function recovery are clinical challenges. It is indispensable to find a suitable material to promote peripheral nerve regeneration due to the limited capacity of peripheral nerve regeneration, which is not an easy task to design a material with good biocompatibility, appropriate degradability. Magnesium has captured increasing attention during the past years as suitable materials. However, there are little types of research on magnesium promoting peripheral nerve regeneration. In this review, we conclude the possible mechanism of magnesium ion promoting peripheral nerve regeneration and the properties and application of different kinds of magnesium-based biomaterials, such as magnesium filaments, magnesium alloys, and others, in which we found some shortcomings and challenges. So, magnesium can promote peripheral nerve regeneration with both challenge and potential.